2013
DOI: 10.1038/jcbfm.2013.27
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Volume Affects Blood–Brain Barrier Integrity in an Acute Transient Stroke Model

Abstract: Insufficient vascular reserve after an ischemic stroke may induce biochemical cascades that subsequently deteriorate the blood-brain barrier (BBB) function. However, the direct relationship between poor cerebral blood volume (CBV) restoration and BBB disruption has not been examined in acute stroke. To quantify BBB integrity at acute stages of transient stroke, in particular for cases in which extravasation of the standard contrast agent (Gd-DTPA) is not observed, we adopted the water exchange index (WEI), a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
1
13
2
1
Order By: Relevance
“…For example, Huang et al . demonstrated that the degree of CBV restoration significantly affects the blood–brain barrier integrity in an acute transient stroke model. In addition to its application to ischemia, our method can also be used to evaluate the activity of tumor angiogenesis and to monitor the effect of antiangiogenic treatment, as the BV and transvascular permeability are important parameters for evaluating angiogenesis .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, Huang et al . demonstrated that the degree of CBV restoration significantly affects the blood–brain barrier integrity in an acute transient stroke model. In addition to its application to ischemia, our method can also be used to evaluate the activity of tumor angiogenesis and to monitor the effect of antiangiogenic treatment, as the BV and transvascular permeability are important parameters for evaluating angiogenesis .…”
Section: Discussionmentioning
confidence: 97%
“…Transvascular permeability was quantified by calculating the WEI . Assuming no exchange of CA between intravascular and extravascular compartments, the apparent fractional BV (Vappα) can be calculated as follows : Vappα=0.25emnormalSnormalIposttissuenormalSnormalInormalpnormalrnormaletissuenormalSnormalIpostbloodnormalSnormalInormalpnormalrnormaleblood.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ROC, VEC or SUG cannot pass through a healthy and mature blood-brain barrier (BBB) 37,38. However, there is evidence that patients with an impaired BBB function treated with either of these compounds, present autonomic dysfunction, seizures 39 and neuronal cell death 15.…”
Section: Discussionmentioning
confidence: 99%
“…Todavia, pouco se sabe a relação das áreas apresentando captação de contraste na tomografia pós-tratamento endovascular e a área cerebral infartada final. Sugere-se que a captação de contraste ocorra em cérebro que já sofreu danos irreversíveis da isquemia e com isto houve quebra da barreira hematoencefálica (BHE) e lesão da lâmina basal (HUANG et al, 2013). Nos pacientes que receberam trombolítico, a lesão da BHE é mais intensa (DIJKHUIZEN et al, 2002).…”
Section: Discussionunclassified